THE CHARACTERISTIC FEATURES OF MEGALITHIC CULTURE IN THE ARCHITECTURE OF TEMPLES ON THE ISLAND OF JAVA (FROM THE ANCIENT TO THE MIDDLE AND LATE CLASSICAL ERAS) - Martin Pradipta, Rahadian Prajudi Herwindo (Riset Arsitektur (RISA), 2017)
Abstract - Culture is the outcome of human thinking and as such it is closely related to society. One prominent form of culture that is very well known in Indonesia is megalithic culture based on the use of large stones or slabs. The impact this megalithic culture has made on Indonesia is profound, for it already reared its head long before the Hindu-Buddhist culture entered Indonesia, so it has affected this archipelago up to now. In this research study, objects have been employed that had previously been passed over in the process of purposive sampling, that is to say temples that featured a terrace or steps in parts of their complex were sought after. This research project aims to look for the typical characteristics of this megalithic culture in the temple architecture found on Java, and their connection with each of the Hindu-Buddhist eras. The outcome of the analysis indicates that the particular features of the megalithic culture are reflected in the arrangement or lay-out of the mass displaying tiers on teraces or steps, both on site and in the individual constructions, in addition to its orientation facing the mountain or the location of the temple being situated atop a mountain. Height is an indicator of the typical hierarchy found in this megalithic culture, in other words: the higher, the holier. The aesthetic ornaments or elements encountered in megalithic culture are not particularly well-developed, even though it must be admitted that in the final period there are statues and etched stones, albeit none too orderly or detailed. Keywords: Megalithic, temple, mass, hierarchy, aesthetic element